5(x-4)+3x=-2(x+10)+10x

Simple and best practice solution for 5(x-4)+3x=-2(x+10)+10x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x-4)+3x=-2(x+10)+10x equation:


Simplifying
5(x + -4) + 3x = -2(x + 10) + 10x

Reorder the terms:
5(-4 + x) + 3x = -2(x + 10) + 10x
(-4 * 5 + x * 5) + 3x = -2(x + 10) + 10x
(-20 + 5x) + 3x = -2(x + 10) + 10x

Combine like terms: 5x + 3x = 8x
-20 + 8x = -2(x + 10) + 10x

Reorder the terms:
-20 + 8x = -2(10 + x) + 10x
-20 + 8x = (10 * -2 + x * -2) + 10x
-20 + 8x = (-20 + -2x) + 10x

Combine like terms: -2x + 10x = 8x
-20 + 8x = -20 + 8x

Add '20' to each side of the equation.
-20 + 20 + 8x = -20 + 20 + 8x

Combine like terms: -20 + 20 = 0
0 + 8x = -20 + 20 + 8x
8x = -20 + 20 + 8x

Combine like terms: -20 + 20 = 0
8x = 0 + 8x
8x = 8x

Add '-8x' to each side of the equation.
8x + -8x = 8x + -8x

Combine like terms: 8x + -8x = 0
0 = 8x + -8x

Combine like terms: 8x + -8x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| q=3m-3u | | Bt=10t | | y=-73898x+3E+06 | | 9.8x+85.71=-10.2x+85.19 | | x*2-144=0 | | 6n+13=3x+14 | | (2y/3)-(13/2)=1/6 | | 3y=2y+34 | | sin^2(x)-3sin(x)+1=0 | | -4x+15=x^2 | | 36x-96-15x-15+140-20x=80-20x-48x-30 | | 8+2w+w^2= | | 3n^2-16n+12=0 | | sin^2(2x)-3sin(2x)+1=0 | | 3(16-18)/2(10) | | (2v+1)(4+v)=0 | | .4(x+2)=1.4(x+1.5) | | 72x-120-1-32x-16+12x+36=30x-1 | | -4(t-7)-(t+4)=7 | | (4x+12)=0 | | x^2+rx-s=0 | | 4(x-3)-7=3(x+2)+6x | | -8y+6x+9=0 | | 2(1+x)=(25825000) | | 230=-5(6p-4) | | 7i+6=-6 | | 11x-3y=54 | | 9+7(x-6)=3-2(x-9) | | P=4c-(20+c) | | 2x+2=2x+4 | | y=4x^2-20x+25 | | (1.1+4.7)x=22.5 |

Equations solver categories